2020
DOI: 10.1186/s12910-019-0442-2
|View full text |Cite
|
Sign up to set email alerts
|

What is it like to use a BCI? – insights from an interview study with brain-computer interface users

Abstract: Background: The neurotechnology behind brain-computer interfaces (BCIs) raises various ethical questions. The ethical literature has pinpointed several issues concerning safety, autonomy, responsibility and accountability, psychosocial identity, consent, privacy and data security. This study aims to assess BCI users' experiences, selfobservations and attitudes in their own right and looks for social and ethical implications. Methods: We conducted nine semi-structured interviews with BCI users, who used the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 43 publications
(59 reference statements)
1
42
0
Order By: Relevance
“…We found the study in [122] to be very interesting and insightful. Such a study aimed to assess BCI users' experiences, self-observations, and attitudes in their own right and looked for social and ethical implications.…”
Section: Further Readings In Bci Challenges and Current Issuesmentioning
confidence: 88%
“…We found the study in [122] to be very interesting and insightful. Such a study aimed to assess BCI users' experiences, self-observations, and attitudes in their own right and looked for social and ethical implications.…”
Section: Further Readings In Bci Challenges and Current Issuesmentioning
confidence: 88%
“…Could the users adapt to this system as it works at a very high speed? If the system output several incorrect results, could the users avoid negative emotion and continue focusing on the intended command [ 46 ]? If not, there might be more and more wrong outputs and the human–computer system would collapse.…”
Section: Discussionmentioning
confidence: 99%
“…The data material used stems from a qualitative interview study with persons who have used BCIs for therapeutic reasons [30]. Nine semi-structured interviews were conducted with BCI users who have participated in medical BCI studies with persons with physical impairments.…”
Section: Methods and Study Participantsmentioning
confidence: 99%
“…This can be read as further ability expectation imposed upon BCI users: being able to perform BCI actions, knowing that the credit (or agency) will not be attributed to you alone. As has been shown, BCI users get credit for their achievements of BCI training and also are able to take advantage of that even after the BCI research studies had been concluded [30]. However, the credit is not the user's only, but also goes to the engineer(s) who developed the technology.…”
Section: Implicit Ability Expectationsmentioning
confidence: 99%
See 1 more Smart Citation